Flexion Dislocation After Limb Lengthening: Correction With Distal Femoral Osteotomy, Quadriceps Release, and Physeal-Sparing Medial Patellofemoral Ligament (MPFL) Reconstruction - Navya Dandu BS; Michael P. Fice MD; Edward Hur MD; Monica Kogan MD; Adam B. Yanke MD, PhD (SAGE Publishing, 2022)
Background: Patellar instability is a common clinical condition in skeletally immature individuals. Surgical treatment is considered when risk of recurrence is high. Indications: Distal femoral osteotomy is indicated in the setting of obligate flexion dislocation where femoral valgus contributes to a shortened lateral column, with concurrent quadriceps procedures considered for chronic contracture and medial patellofemoral ligament (MPFL) reconstruction for added stabilization. Technique Description: This procedure is performed in a stepwise manner as some components may not be necessary based on the patient's specific anatomy. The procedure begins with a lateral iliotibial (IT) band soft tissue release or lengthening if possible. The distal femoral osteotomy is then performed utilizing a lateral opening wedge technique. Bone graft is placed in a structural fashion to maintain the correction while a locking plate is inserted. In patients with chronic lateral patellar dislocation, correction of bony alignment may not completely restore tracking. If lateral maltracking persists after further distal soft tissue release, a VY-lengthening quadricepsplasty can be considered. To perform this, the vastus lateralis (VL) is first released. In this patient, the patella was able to be stabilized centrally after VL release, and therefore, the VY-plasty was not performed. The soft tissue attachments for the final MPFL reconstruction are then prepared, including two at the superomedial and midbody of the patella and one at the adductor tendon. The whip-stitched graft is then passed through the adductor sling followed by the patellar periosteal tunnels with the knee in slight flexion to ensure centralization within the trochlear groove. Examination under anesthesia before final fixation of the reconstruction should demonstrate 1A lateral translation. Results: Correction of distal femoral valgus with osteotomy, in isolation or in combination with other patellar stabilizing procedures, has demonstrated significant improvement in patient-reported outcomes and reduced redislocation rates. However, large cohort studies are limited. Discussion/Conclusion: Both osseous and soft tissue abnormalities are important to consider in since they can contribute in varying degrees to patellar maltracking. Therefore, assessment of patellar tracking should be performed frequently to guide extent of surgical correction necessary.